(untitled) (TAMADDUN NURI JURNALI, 2024)
This article analyzes the economic cooperation relations of the Republic of Uzbekistan in the international arena today with its strategic location, wealth of natural resources, and developing relations with the Kingdom of Saudi Arabia, which is one of the leaders among the Arab countries, which is one of the economic centers of the world.